Customer-perceived value of e-financial services: a means-end approach. (31st January 2006) - Laukkanen, Tommi
The financial services sector has recently undergone changes unprecedented in its history. Understanding customers' needs and values has become more important for financial institutions than ever before, not only due to the changing environment but also because of changed customer behaviour. This study explores the customer-perceived value of two e-financial services, namely electronic fund transfer service and internet brokerage service. This is done by using a means-end approach. It is a qualitative in-depth interviewing method that is used for explaining how product or service attributes facilitate consumers' achievement of desired end-states of being. The results indicate how different electronic services create value for customers in service consumption. The findings provide banking executives with a better understanding of what kind of value customers perceive in the consumption of different e-financial services. The results indicate similarities and differences in the customer-perceived value between the services explored.